The Participation of the Young Generation as Palm Oil Farmers in Good Practices of Sustainable Palm Oil Plantations in North Sumatra and Aceh - Pulungan, Delyana Rahmawany; Saragih, Dina Arfianti; Tanjung, Yulia Windi; Aznur, Tifany Zia (International Journal of Economics Development Research (IJEDR), 2024)
In this study, it was found that the younger generation plays an important role in the management of palm oil plantations to assist in the inclusivity of sustainable development through positive palm oil campaigns. The urgency of involving the younger generation is necessary to face sustainability challenges. Although sustainability is a primary focus in the palm oil industry, the involvement of the younger generation in the management of plantations is still limited. This research aims to understand the involvement and perceptions of the younger generation as oil palm farmers in the good practices of sustainable oil palm plantations. The implementation of research in the provinces of North Sumatra and Aceh. The research sample consisted of 384 oil palm farmers. The research method is a case study with descriptive qualitative data analysis techniques using SPSS Version 22. The analysis results show that only 37,24% of palm oil farmers are young, under 45 years old, while more than 62,76%, are involved in good palm oil plantation practices, >45 years old. Their perception is also known to fall into the category of poor (score of 54) regarding good practices in palm oil plantations. The main issue is the unfavourable demographic structural changes for the agricultural sector, where the number of elderly farmers (over 55 years old) is increasing, while the workforce of young people is decreasing. The phenomenon of aging farmers and the declining interest of young labor in the agricultural sector is becoming more pronounced.